Knowledge management and challenging roles of academic librarians. - Yaacob, Raja Abdullah; Jamaluddin, Adnan; Jusoff, Kamaruzaman (Canadian Research & Development Center of Sciences and Cultures, 2010)
With globalization the credibility of the workforce is determined by how best they can accommodate themselves in the growing challenges of k-economy. Knowledge Management (KM) has been in operation for quite some time. Its close affinity to library and information management is undeniable. Library has not relinquished its role and interest as information and knowledge providers. It is fitting then to recognise that a well planned strategy, involving the library and the management of the institution could provide significant influence to achieve the KM objectives. Librarians and information professionals (IPs) should be dedicated to fulfilling the varied information needs of the users, amidst the K-economy by providing accurate and relevant bibliographic and physical access and offer referral to the multidimensional range of information within the library premise and outside. KM is a challenge to the information professionals and for the fields of librarianship and information science and needs to be taken seriously to leverage the intellectual assets and to facilitate knowledge utilization and creation. Key words: K-economy; Knowledge management (KM); Globalization; Library management; Information management